Is remdesivir the therapeutic answer for COVID-19: a review of current knowledge - Ahsan, Marya; Mallick, Ayaz Khurram (International Journal of Basic & Clinical Pharmacology, 2020)
As the world races to find the solution to the COVID-19 pandemic, an investigational agent which has triggered worldwide interest is remdesivir. Though failing clinical trials for treatment of Ebola virus disease, remdesivir has shown efficacy in numerous viral studies involving SARS-CoV-2. Reports from compassionate use of remdesivir in hospitalized patients of COVID-19 have been promising. But the real picture about the safety and efficacy of remdesivir can only be known after completion of randomized clinical trials. In this review, we aim to highlight the salient features of pharmacokinetics and pharmacodynamics of remdesivir known so far and its plausible role in management of COVID-19. We searched the PubMed database and Google Scholar for published literature using the key words: remdesivir, human coronavirus, novel coronavirus, COVID-19, SARS-CoV 2, mechanism of action, pharmacokinetics, pharmacodynamics and compassionate use till 1st May 2020. The U. S. national library of medical trials registry was searched for ongoing trials with remdesivir among patients of COVID-19. Remdesivir is a prodrug of a nucleoside Analog that inhibits RNA replication by binding to viral RNA dependent RNA polymerase. It is being employed in many global phase-3 clinical trials for evaluating the efficacy and safety of the drug in patients of COVID-19.